Urethra-sparing prostate cancer radiotherapy: Current practices and future insights from an international survey - Jennifer Le Guévelou; Paul Sargos; Piet Ost; Filippo Alongi; Stefano Arcangeli; Alejandro Berlin; Pierre Blanchard; Anna Bruynzeel; Olivier Chapet; Alan Dal Pra; Robert T. Dess; Matthias Guckenberger; et al. (Clinical and Translational Radiation Oncology)
Purpose: In prostate cancer patients, high radiation doses to the urethra have been associated with an increased risk of severe genitourinary toxicity following dose-escalated radiotherapy. Urethra-sparing techniques have emerged as a promising approach to reduce urinary toxicity. This international survey aims to evaluate current global practices in urethra-sparing and explore future directions for the implementation of this technique in external beam radiotherapy (EBRT) for prostate cancer. Methods and materials: In April 2024, a survey consisting of 20 questions was distributed to 26 international radiation oncology experts in prostate cancer EBRT, with 23 experts participating. The survey focused on clinical scenarios which might take benefit from urethra-sparing, the definition of the urethra and urinary organs-at-risk, and urethral dose constraints. Results: Magnetic resonance imaging with T2-weighted sequences is the preferred method for urethra contouring (83 % consensus). Based on the experts opinion, urethra-sparing should be considered for prostate cancer EBRT, regardless of pelvic irradiation, except in cases where the tumor is located within 2 mm of the urethra and/or transitional zone, or in T4 disease. Most experts would not apply specific dose constraints to the urethra for either conventional or moderate hypofractionation regimens. When delivering stereotactic body radiotherapy (SBRT), urethra-sparing with dose hotspot limitation (urethra steering) is recommended by 70 % of the experts, in particular when combined with focal boosting (91 %). Urethra dose-reduction is also the favored approach for salvage prostate reirradiation with SBRT (70 % agreement). Large variations exists regarding urethral dose constraints. Conclusions: Urethra-sparing is a promising technique for the mitigation of urinary toxicity in prostate cancer patients undergoing EBRT, particularly recommended for ultra-hypofractionation and reirradiation with SBRT. The lack of consensus on specific urethral dose constraints and optimal sparing techniques underscores the need for further research to standardize practices in this field.